2006
DOI: 10.1159/000093010
|View full text |Cite
|
Sign up to set email alerts
|

Sympathectomy Causes Aggravated Lesions and Dedifferentiation in Large Rabbit Atherosclerotic Arteries without Involving Nitric Oxide

Abstract: Previously [Histochem J 1997;29:279–286], we found that sympathectomy induced neointima formation in ear but not cerebral arteries of genetically hyperlipidemic rabbits. To clarify the influence of sympathetic nerves in atherosclerosis, and whether their influence involves vascular NO activity, we studied groups of normocholesterolemic intact (NI) and sympathectomized (NS), and hypercholesterolemic intact (HI) and sympathectomized (HS) rabbits (diet/6-hydroxydopamine for 79 days). Segments of basilar (BA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 131 publications
(105 reference statements)
2
10
0
2
Order By: Relevance
“…To the best of our knowledge, data supporting our observations only exist for h-caldesmon (Kacem et al 2006, Hachani et al 2010. The expression levels of RhoK did not differ between denervated and control arteries.…”
Section: Sympathetic Nerves Control Ca 2+ Sensitivity Of Arterial Consupporting
confidence: 66%
“…To the best of our knowledge, data supporting our observations only exist for h-caldesmon (Kacem et al 2006, Hachani et al 2010. The expression levels of RhoK did not differ between denervated and control arteries.…”
Section: Sympathetic Nerves Control Ca 2+ Sensitivity Of Arterial Consupporting
confidence: 66%
“…A number of previous experimental studies have reported that sympathetic denervation promoted atherosclerosis at sites remote to the denervation procedure (Murphy et al, 1957; Snyder and Campbell, 1958; Kacem et al, 1997, 2006; Kacem and Sercombe, 2008; Hachani et al, 2010). Bilateral surgical lumbar sympathectomy has been reported to increase atherosclerosis severity in the thoracic and abdominal aorta, and iliac and femoral arteries in rabbits fed a high cholesterol diet (Murphy et al, 1957; Snyder and Campbell, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental studies suggest that both chemical and surgical sympathetic denervation promote atherosclerosis (Murphy et al, 1957; Snyder and Campbell, 1958; Kacem et al, 1997, 2006; Kacem and Sercombe, 2008; Hachani et al, 2010). A recent study reported that RDN inhibited atherosclerosis formation in normotensive apolipoprotein E-deficient (ApoE −/− ) mice fed a high-fat diet (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that sympathetic drive promotes and/or maintains SMC differentiation, its absence leading to dedifferentiation of ''contractile'' SMCs towards a highly ''synthetic'' phenotype [9,23,24]. Therefore, we postulate that the aortic structural remodeling observed in the present study was primarily the direct result of sympathetic nerve blockade to the aorta, independent of hemodynamic changes, with the increase in extracellular matrix proteins attributed to post-sympathectomy excessive SMC synthetic activity.…”
Section: Discussionmentioning
confidence: 99%